1983
DOI: 10.1111/j.1943-278x.1983.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

On Precipitating Factors: Cancer as a Cause of Suicide

Abstract: This case-control study provides individual-based data describing the impact of being a cancer patient on the odds of suicide. 5,009 suicides and 17,064 controls are compared. The data indicate that cancer patients are 50 to 100 percent more likely than nonpatients to commit suicide. This and other studies indicate that health status should be considered in future attempts to relate suicide to social environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Physical illness Bagley et al (1976); Bastia & Kar (2009); Blackmore et al (2008); Chynoweth et al (1980); Conner et al (1999); Conwell et al (1990); Fang et al (2008); Harris & Barraclough (1997); Harwood et al (2006); Heikkinen & Lönnqvist (1995); Hem et al (2004); Hunt et al (2009); ; Llorente et al (2005); Marshall et al (1983);Miller et al (2008); Obafunwa & Busuttil (1994); Quan & Arboleda-Florez (1999); Rubenowitz et al (2001); Timonen et al (2002); Walker et al (2008).…”
Section: Physical Illnessmentioning
confidence: 99%
“…Physical illness Bagley et al (1976); Bastia & Kar (2009); Blackmore et al (2008); Chynoweth et al (1980); Conner et al (1999); Conwell et al (1990); Fang et al (2008); Harris & Barraclough (1997); Harwood et al (2006); Heikkinen & Lönnqvist (1995); Hem et al (2004); Hunt et al (2009); ; Llorente et al (2005); Marshall et al (1983);Miller et al (2008); Obafunwa & Busuttil (1994); Quan & Arboleda-Florez (1999); Rubenowitz et al (2001); Timonen et al (2002); Walker et al (2008).…”
Section: Physical Illnessmentioning
confidence: 99%
“…Deterioration in health is associated with increased suicide rates, perhaps especially among elderly women (Bourque et al, 1983) and alcoholics (Motto, 1980). One review of multiple studies concluded that getting cancer increases the suicide rate by as much as double (Marshall, Burnett, & Brasurel, 1983).…”
Section: Falling Short Of Standardsmentioning
confidence: 99%
“…Earlier investigations into the association between suicide and medical illness reported suicide to be the cause of patients' deaths in 10.9-51.0% of cases [64]. Patients with cancer [65][66][67] and diseases of the central nervous system (CNS) including multiple sclerosis [68][69][70] and Huntington's disease [71,72] were at greater risk of committing suicide as were older patients with chronic illness. As AIDS is a terminal disease which affects all organ systems [73] including the CNS, it is not unreasonable to expect that HIV/AIDS may also be associated with a greater risk of suicidal behaviour [6].…”
Section: Comparison Of Suicide In Hiv/aids With Other Medically Ill Populationsmentioning
confidence: 99%